Coverage of Japanese encephalitis routine vaccination among children in central India. Issue 1 (30th September 2022) - Tandale, Babasaheb V.; Deshmukh, Pravin S.; Narang, Rahul; Qazi, Mohiuddin S.; Padmaja, Goteti V.; Deshmukh, Pradeep R.; Raut, Abhishek V.; Narlawar, Uday W.; Jha, Punam Kumari; Rajderkar, Shekhar S.; ,
Abstract: We aimed to estimate the coverage of Japanese encephalitis (JE) vaccination in central India to help explain the continued occurrence of JE disease despite routine vaccination. We implemented a 30‐cluster survey for estimating the coverage of JE vaccination in the medium‐endemic areas implemented with JE vaccination in central India. The parents were enquired about the uptake of the JE vaccine by their children aged 2−6 years, followed by verification of the immunization cards at home along with reasons for non‐vaccination. Vaccination coverage was reported as a percentage with 95% confidence intervals (CI). We estimated high coverage of live‐attenuated SA 14‐14‐2 JE vaccination in Maharashtra (94.8%, 95% CI: 92.7−96.3) and Telangana (92.8%, 95% CI: 90.0−94.9). The vaccination card retention was 90.3% in Maharashtra and 70.4% in Telangana state. There were no gender differences in coverage in both states. A similar level of JE vaccination coverage was observed during the year 2013−2021 in both states. In Maharashtra, the maximum age‐wise coverage was 96.6% in the >60 months age category, whereas in Telangana it was in the <24 months age category (97.2%). The timeliness of JE vaccination was appropriate and similar in both states. We found a very good agreement between JE and measles‐rubella vaccinations administered simultaneously. The reasons for non‐vaccination were the shortage of vaccines and the parental migration for work. The coverage of JE vaccination was high in medium‐endemic regions in central India. Vaccination effectiveness studies may help further explain the continued incidence of JE.